Potential for increasing groundnut production in Tanzania by enhancing technical efficiency: A stochastic meta-frontier analysis - Das, Abhishek; Kumar, Shalander; Ganga Rao, N. V. P. R. (Frontiers in Sustainable Food Systems, 2023)
Groundnut crop is one of the major sources of financial and food security for a large number of Tanzanian smallholder farmers. However, the production of groundnuts in Tanzania is underdeveloped, and yields are reportedly 2.5 to 3 times lower than in other African nations such as Nigeria. There are a number of factors that contribute to lower yields including the cultivation of outdated plant varieties, increased climate variability, the infestation of pests and diseases, and the use of outdated farming techniques. To analyze the scope for increasing groundnut production, this study investigates and compares the technical efficiencies (TEs) and technological gap ratios (TGRs) in Tanzania's four main groundnut-producing regions, namely the Central zone, Lake Zone, Southern zone, Southern highland zone, by using a two-step meta frontier model. We used ICRISAT data collected under the Tropical Legume-III project during 2017–18. Our results show a very low level of technical efficiency of groundnut production in the regions and significant regional differences in TEs, TGRs, and Meta Technical Efficiencies (MTEs). The study identifies a tremendous scope to increase groundnut productivity and production in Tanzania by enhancing its production efficiency and the key drivers that may help harness this potential.